2009
DOI: 10.1039/b822959g
|View full text |Cite
|
Sign up to set email alerts
|

A generalized theoretical model for “continuous particle separation in a microchannel having asymmetrically arranged multiple branches”

Abstract: In this article we present a generalized theoretical model for the continuous separation of particles using the pinched flow fractionation method. So far the theoretical models have not been able to predict the separation of particles without the use of correction factors. In this article we present a model which is capable of predicting the separation from first principles. Furthermore we comment on the importance of the incorporation of the finite height of the micro fluidic channels in the models describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…Channel geometry, particle size, fluid transport, and volumetric flow ratio of input‐channel fluids are all known to affect the trajectories of particle motion through the device. Andersen et al recently developed a model based on the laminar velocity profile in a rectangular channel and assuming that particles leave the top corner of the pinch and follow the fluid streamlines into different exit or drain channels depending on particle size. This model provides better agreement with experiments than previous models.…”
Section: Introductionmentioning
confidence: 99%
“…Channel geometry, particle size, fluid transport, and volumetric flow ratio of input‐channel fluids are all known to affect the trajectories of particle motion through the device. Andersen et al recently developed a model based on the laminar velocity profile in a rectangular channel and assuming that particles leave the top corner of the pinch and follow the fluid streamlines into different exit or drain channels depending on particle size. This model provides better agreement with experiments than previous models.…”
Section: Introductionmentioning
confidence: 99%
“…The desire to generate isolation systems that are more readily amenable to diagnostic use has led to a growth in the design of microfluidic, lab-on-a-chip type systems capable of separating and capturing particles of different sizes. Many techniques have been developed using microfluidics to separate microparticles, using methods such as a combination of centrifugal force and graduated mechanical gap (Maruyama et al 2010), flow splitting and recombining (so-called biomimetic devices that rely on size-based variations in particle behavior when in laminar flow) (Takagi et al 2005;Yamada and Seki 2006;Andersen et al 2009); optical fractionation (MacDonald et al 2003;Ladavac et al 2004;Milne et al 2007;Smith et al 2007), or deterministic lateral displacement arrays, which function much like a particle sieve (Huang et al 2004;Mohamed et al 2004;Loutherback et al 2010). Research has also demonstrated that it is possible to isolate shed microvesicles from the cells of origin based on size discrimination using dielectrophoretic sorting.…”
Section: Isolation and Separation Formats For Shed Vesicle Populationsmentioning
confidence: 99%
“…This modification is capable of separating 1 µm and 2.1 µm particles with an efficiency of 80%. Additionally, the broadening of the pinched segment allows adding downstream collecting channels in the PFF design [337]. Alternatively, the separation resolution was enhanced by a simple geometric modification of the primary PFF design like adding a snakelike part to channel [338].…”
Section: Pinched Flow Fractionationmentioning
confidence: 99%